Have a little faith [compact disc, unabridged] : a true story - Albom, Mitch, 1958- (Hyperion Audio, 2009)
When an eighty-two-year-old rabbi from Albom's old hometown asks him to deliver his eulogy, Albom goes back to his nonfiction roots and becomes involved with a Detroit pastor--a reformed drug dealer and convict--who preaches to the poor and homeless in a decaying church with a hole in its roof. A timely, moving, and inspiring look at faith: not just who believes, but why.